Embryo production of two sympatric snapping shrimps of the genus Alpheus (Caridea: Alpheidae) from Northeastern Brazil: A comparative approach - Soledade, Guidomar Oliveira; Santos, Patricia Souza; Pescinelli, Régis Augusto [UNESP]; Costa, Rogério Caetano [UNESP]; Almeida, Alexandre Oliveira (Springer Nature, 2017)
In spite of the high number of species (~ 300) and their wide geographic distribution, studies on reproductive biology have only been conducted with a few species of the genus Alpheus Fabricius 1798. The objective of this study was to compare the characteristics of embryo production of two sympatric species of shrimps, Alpheus buckupi Almeida, Terossi, Araújo-Silva & Mantelatto, Zootaxa 3652:437-452, 2013a and A. carlae Anker, Zootaxa 3386:1-109, 2012. Brooding females were collected in two sites on the coast of Bahia, northeastern Brazil, between July 2012 and May 2013. Female’s carapace length (CL) was measured and their embryos were classified according to stage of development. A total of 47 females of A. buckupi (mean CL 9.4 ± 1.0 mm) and 36 of A. carlae (mean CL 8.6 ± 1.3 mm3) were sampled. Fecundity was positively correlated with CL in both species. Fecundity was higher (117 ± 80) in A. buckupi, which also produced smaller embryos (0.10 ± 0.03 mm3)thanA. carlae (0.13 ± 0.03 mm3; fecundity: 50 ± 58). The reproductive output (RO) of A. buckupi and A. carlae was similar, 0.05 ± 0.06 and 0.04 ± 0.02, respectively. The fecundity and reproductive output of both species were lower than those reported for other alpheids. Our results indicated that sympatric lineages differ regarding reproductive features, suggesting that different selective forces influenced fecundity in these snapping shrimps. This study provides the first insights on the embryo production of A. buckupi in the Western Atlantic and of A. carlae in northeastern Brazil.
Keywords: Crustacea; Embryo volume; Maternal output; Reproduction